Bumblebee workers avoid foraging in road verges along busy roads - Sofia Blomqvist; Henrik G. Smith; Björn K. Klatt; Lina Herbertsson (Basic and Applied Ecology)
Road verges can harbour a diversity of flowering plants and may be useful foraging habitats for pollinating insects in landscapes where flower-rich habitats are scarce. Targeted management of road verges can further enhance flower abundance, thereby potentially benefitting flower-visiting insects. However, traffic on the adjacent road could pose a risk, such that flower-rich road verges instead act as ecological traps, attracting flower-visiting insects to a hazardous environment. To investigate the suitability of road verges for the implementation of pollinator promoting actions, it is important to understand the risks associated with these habitats. By placing three commercial bumblebee colonies with individually tagged workers at each of 12 road verges, we studied whether traffic intensity influenced individual worker mortality, worker behaviour, and colony growth. We visited the colonies weekly to determine how frequently workers leaving the nest headed towards the nearest road verge and, when crossing the road, at what height they did so. Only 10 % of the departing workers were observed to cross the road and 65 % of these crossings occurred higher than 1.5 m, corresponding to the height of an average passenger car. The proportion of bees heading towards the nearest road verge when leaving the nest declined with traffic intensity. About 22 % headed towards road verge at 100 vehicles/24 h, whereas only 7 % departed in this direction at 20,000 vehicles/day. We suggest that the bumblebees avoided foraging in road verges with disturbing turbulence from passing vehicles, potentially protecting them from traffic-related mortality. Indeed, we found no evidence for traffic to influence individual worker mortality or colony weight change. We conclude that traffic does not pose a severe threat to bumblebee workers, as they avoid flying towards the road. The benefit of adapted management may therefore be limited by traffic and should be targeted to roads with low traffic.